The influencing factors of college students’ legal emotion and the mechanism of its effect on aggressive behavior - Xu, Shuhui; Yu, Junwen; Fan, Lu; Yang, Qingmei; Wang, Zhiqiang; Zhang, Yuanyuan (Frontiers in Psychology, 2024)
Current research has increasingly focused on the preventive role of individual legal socialization in crime. The socialization of legal emotions is an important part of legal socialization. Building upon existing literature, this study, conducted through two sub-studies, investigated the influencing factors of legal emotions in N mainland Chinese university students and the mechanisms through which legal emotions impact aggressive behavior. In study 1, the results indicated that mother-child attachment, innovation spirit, and positive emotional expression positively predicted positive legal emotion, while mother-child attachment, dependency dimension in adult attachment, and positive emotional expression negatively predicted negative legal emotions. The anxiety dimension in adult attachment and negative emotional expression positively predicted negative legal emotions. In study 2, Positive legal emotion among university students could directly negatively predict aggressive behavior or exert influence through social alienation. Negative legal emotions could not only directly positively predict aggressive behavior but also partly affect it through social alienation. In summary, our study not only identified factors that influence legal emotions, but also found that legal emotions have an impact on aggressive behavior directly or indirectly through social alienation. Our research findings have significant implications for cultivating positive legal emotion in university students and curbing aggressive behavior. This can be achieved by promoting the legal socialization of university students and ultimately contributing to crime prevention.